The Prevalence of Celiac Disease-Specific Auto-Antibodies in Type 1 Diabetes in a Moroccan Population - Ider Oujamaa; Majda Sebbani; Lahcen Elmoumou; Aïcha Bourrahouate; Rabiy El Qadiry; Soufian El Moussaoui; Imane Ait Sab; Mohamed Sbihi; Laila Ennazk; Ghizlane El Mghari-Tabib; Nawal El Ansari; Hicham Baizri; et al. (International Journal of Endocrinology)
Objective. We aimed to determine the prevalence of specific auto-antibodies to celiac disease (CD) in Moroccan type 1 diabetic (T1D) patients and compare the clinical and biological characteristics of seropositive and seronegative cases. Patients and Methods. A cross-sectional study was carried out on 276 T1D patients including 109 adults and 167 pediatric cases. The screening for CD was performed by an Elisa IgA anti-tissue transglutaminase antibody (tTGA) testing, combined with IgA quantification by nephelometry. Positive-IgA-tTGA cases were secondly tested for anti-endomysial antibodies (EMA) using an immunofluorescence technique, and the IgA deficiency cases were screened for IgG-tTGA. Patients with low positive tTGA titers underwent HLA-DQ2/DQ8 typing. Sociodemographic and clinical data of the patients were collected using a hetero-administered questionnaire. The comparison of clinical and biological data between seropositive and seronegative diabetics was done using independent T, Mann–Whitney U, chi-squared, and Fisher tests, which were considered significant if p value <0.05. Results. The prevalence of CD-specific auto-antibodies was estimated to be 9.1% (IC = 95%), with 25 positive cases in tTGA and EMA testing. Eight cases displayed low titers of IgA-tTGA, among which 4 were positive for HLA-DQ2, 1 for HLA-DQ8, and 1 for both DQ2 and DQ8. The other 2 cases had a biopsy-proven CD. Compared to seronegative patients, seropositive cases had a higher percentage of associated autoimmune disorders (16% vs. 2.4%, p=0.008), with a significant lower height Z-scores (median: −0.90 (−3.93 to 0.95) vs. −0.51 (−4.54 to 2.18), p=0.029) and a higher HbA1c level (median: 11.30% (7.31 to 16.00) vs. 9.30% (4.40 to17.31), p=0.022). Conclusion. The current study gave evidence of a high prevalence of CD specific auto-antibodies in T1D population. The co-existence of these two conditions was associated with a poor glycemic control, a lower height, and other autoimmune diseases. These findings may suggest the necessity of a systematic screening of CD in T1D patients.